Advanced nanomaterial for prostate cancer theranostics - Hao, Bin; Wei, Li; Cheng, Yusheng; Ma, Zhifang; Wang, Jingyu (Frontiers in Bioengineering and Biotechnology, 2022)
Prostate cancer (PC) has the second highest incidence in men, according to global statistical data. The symptoms of PC in the early stage are not obvious, causing late diagnosis in most patients, which is the cause for missing the optimal treatment time. Thus, highly sensitive and precise early diagnosis methods are very important. Additionally, precise therapy regimens for good targeting and innocuous to the body are indispensable to treat cancer. This review first introduced two diagnosis methods, containing prostate-specific biomarkers detection and molecular imaging. Then, it recommended advanced therapy approaches, such as chemotherapy, gene therapy, and therapeutic nanomaterial. Afterward, we summarized the development of nanomaterial in PC, highlighting the importance of integration of diagnosis and therapy as the future direction against cancer.